Avaliação da aplicação de areia descartada de fundição em bases e sub-bases de pavimentos asfálticos - Morais, Manuella de (2019)
Products from the foundry industries are essential to numerous production chains, such as transportation and automation. However, the generation of residual by-products is significant, motivating a high environmental concern with their final destination. In this sense, the present work aims to promote a technically and environmentally viable application for the sand waste from foundry produced in a foundry industry in the city of Erechim-RS. For this purpose, it was proposed to incorporate different levels of ADF as aggregate in mixtures with three other materials traditionally used in the construction of pavement bases and sub-bases, using the granulometric stabilization technique. The four materials were characterized in terms of granulometric aspects, which made it possible to design mixtures in order to satisfy two working ranges (“A” and “E”) specified by the federal agency that controls the construction of highways. In addition, the organ's specifications regarding Atterberg limits and abrasion wear were also met by the materials. The mixtures with different levels of ADF, molded in optimum conditions, were then subjected to mechanical tests of California Bearing Ratio (CBR) and Resilient Modulus (MR). The projected mixtures with contents of 12% and 2% of ADF (range "A" and "E", respectively) showed the highest support capacity, reaching an CBR of 267.50% and 111.35%, respectively. In the case of range“ A”, the addition of ADF improved the support characteristics of the mixture. The highest values of MR were observed for mixtures containing levels of 12% and 38% (ranges "A" and "E", respectively), however, the variation of the ADF content within each range did not cause great variability in terms of resilient characteristics. Through these tests, it was found that the addition of ADF to the working ranges "A" and "E" at maximum levels of 12% and 38%, respectively, guarantees a structure of high density, resistance and little susceptible to deformations, it can be used for the construction of pavement bases and sub-bases, without any technical damage. The environmental classification of the mixture containing 38% ADF content concluded that it is a Non-Inert residue - Class II A and therefore, proves the environmental viability of the mixture for use in pavements and sub- floors.